Application of the Fingerprint System as a Discipline Control Tool for Educators and Education Personnel - Ellya Rohati; Reny Oktafia; Istikomah Istikomah (Proceedings of The ICECRS, 2020)
This study is to determine whether the application of fingerprint attendance can be used as a tool to control performance discipline. This study uses a qualitative description method with the interview method, data collection in the form of documents. Data validation with triangulation techniques. The results of data analysis show that the fingerprint system simplifies the presence process so that the fingerprint system can be used as a disciplinary control tool because all attendance data can be stored.